2015
DOI: 10.1063/1.4913587
|View full text |Cite
|
Sign up to set email alerts
|

All-perovskite transparent high mobility field effect using epitaxial BaSnO3 and LaInO3

Abstract: We demonstrate an all-perovskite transparent heterojunction field effect transistor made of two lattice-matched perovskite oxides: BaSnO3 and LaInO3. We have developed epitaxial LaInO3 as the gate oxide on top of BaSnO3, which were recently reported to possess high thermal stability and electron mobility when doped with La. We measured the dielectric properties of the epitaxial LaInO3 films, such as the band gap, dielectric constant, and the dielectric breakdown field. Using the LaInO3 as a gate dielectric and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

4
100
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 116 publications
(104 citation statements)
references
References 21 publications
4
100
0
Order By: Relevance
“…In 2012, Kim et al reported that a La-doped BaSnO 3 (space group P m3m, cubic perovskite structure, a = 4.115Å, E g ∼ 3.1 eV) single crystal grown by the flux method exhibits a very high mobility (μ Hall ∼ 320 cm 2 V −1 s −1 ) at room temperature [2,3]. This report inspired the current interest in BaSnO 3 films and BaSnO 3 -based TFTs [4][5][6][7][8][9].Since the mobility is expressed as μ = eτ m * −1 , where e, τ , and m * are the electron charge, carrier relaxation time, and carrier effective mass, respectively, the high mobility of the Ladoped BaSnO 3 single crystal should be due to both a small m * and a large τ . Generally, the τ value of epitaxial films is smaller than that of the bulk single crystal due to the fact that the carrier electrons are scattered at dislocations, which originated from the lattice mismatch (δ) and at other structural defects, in addition to optical phonon scattering.…”
mentioning
confidence: 66%
“…In 2012, Kim et al reported that a La-doped BaSnO 3 (space group P m3m, cubic perovskite structure, a = 4.115Å, E g ∼ 3.1 eV) single crystal grown by the flux method exhibits a very high mobility (μ Hall ∼ 320 cm 2 V −1 s −1 ) at room temperature [2,3]. This report inspired the current interest in BaSnO 3 films and BaSnO 3 -based TFTs [4][5][6][7][8][9].Since the mobility is expressed as μ = eτ m * −1 , where e, τ , and m * are the electron charge, carrier relaxation time, and carrier effective mass, respectively, the high mobility of the Ladoped BaSnO 3 single crystal should be due to both a small m * and a large τ . Generally, the τ value of epitaxial films is smaller than that of the bulk single crystal due to the fact that the carrier electrons are scattered at dislocations, which originated from the lattice mismatch (δ) and at other structural defects, in addition to optical phonon scattering.…”
mentioning
confidence: 66%
“…On the other hand, compared with the other FET which used the perovskite LaInO 3 (LIO) dielectric layer and BLSO channels, our FET showed smaller µ FE and similar I on /I off ratio. 18 Since the doping level of the BLSO channel in our case is 0.5% while that of LIO/BLSO FET is 0.07%, the increased impurity scattering is probably responsible for the reduced µ FE . Recently reported FETs successfully used a 10 nm thick epitaxial perovskite Sr 0.5 Ba 0.5 SnO 3 (SBSO) dielectric layer in combination with organic polymer parylene as the gate oxide on the undoped BSO channel.…”
Section: Channels and Different Gate Oxides © 2017 Author(s) All Armentioning
confidence: 99%
“…Since the report of an extraordinary high room temperature mobility of 320 cm 2 /Vs for La:BaSnO 3 single crystals [1], which is the highest value reported for perovskite oxides, the material has rapidly attracted interest as high-mobility channel layer in oxide thin film transistors [2][3][4] and multi-functional perovskite-based optoelectronic devices [5,6]. To fully exploit the potential of La: BaSnO 3 for device applications, current research concentrates on understanding and improving the electron transport in epitaxial La:BaSnO 3 thin films [7][8][9][10][11][12][13][14].…”
mentioning
confidence: 99%